Rank and Representation: A Quantitative Analysis of Female Representation Within Entry Level Faculty Positions - Nicholson, Nicole (Advances in Social Sciences Research Journal, 2020)
The representation of women in leadership positions and as tenured faculty in higher education has been an issue of concern for a number of years across academic disciplines. What remains unclear is whether this trend is also observed all the way down to entry-level positions in the field of education alone. The purpose of this quantitative, correlational study was to determine if women and men occupying the non-tenured track ranks of assistant and associate professor were equally represented in the field of education at post-secondary, credential granting institutions in California (n=46). Between groups comparisons indicated that female, assistant professors significantly outnumbered men at both public and private California universities (p<0.0001), and outnumbered men as associate professors at private universities (p=0.0148). Within groups comparisons indicated that while fewer in number, a greater percentage of men occupied the rank of associate professor, thus outranking their female colleagues at public and private learning institutions (54.5% and 44.8%, respectively). However, the difference was not statistically significant.